U.S. Global Logistics and Transport A Computable General Equilibrium Model (Global Journal of Human-Social Science, 2014)
Global logistics companies can reduce the cost of international trade and increase consumer welfare. By reducing total transportation costs and increasing production and distribution efficiencies, these companies allow both exporting and importing countries to use fewer scarce resources to meet the needs of producers and consumers. This paper will employ a computable general equilibrium (CGE) model to quantify the economic impacts of global logistics companies in United States. As a major exporter and importer of goods and services, the United States is in a position to affect the consumer welfare of people around the globe. The CGE model will measure the effect of lowering costs in transportation and logistics for trade between the United States and the world. Results show significant increases in trade and consumer welfare, and interesting shifts in production and consumption. The United States in particular would stand to benefit.